Navigating workplace uncertainty: a path analysis of perceived overqualification, covert narcissism, workplace alienation, and role ambiguity among nurses - Heba Sobhy Mohamed; Mohammed Adel Abd Elhafeez Elbakry; Ahmed Abdellah Othman; Mohamed Hussein Ramadan Atta; Abeer Moustafa Barakat; Alaa Eldin Moustafa Hamed (BMC Nursing)
Abstract Background Perceived overqualification is an emerging challenge in the nursing workforce, influencing job satisfaction, psychological well-being, and overall retention. This study aims to examine the relationships among perceived overqualification, covert narcissism, workplace alienation, and role ambiguity among nurses using path analysis to explore their interactions. Methods A cross-sectional study was conducted with 446 nurses from various Egyptian healthcare settings. Data was collected through structured face-to-face interviews using four validated instruments: the Scale of Perceived Overqualification (assessing subjective overqualification), Hypersensitive Narcissism Scale (measuring covert narcissism), Role Ambiguity Scale (evaluating clarity in job responsibilities), Work Alienation Scale (assessing workplace alienation), Additionally, a researcher-developed Demographic Questionnaire was used to collect participants’ background characteristics. Path analysis was conducted using AMOS 26.0 to test direct and indirect relationships among variables, with model fit assessed using standard indices. Results Direct effects revealed that perceived overqualification significantly predicted workplace alienation (B = 0.401, 95% CI [0.311, 0.490], p <.001), covert narcissism (B = 0.430, 95% CI [0.193, 0.423], p <.001), and role ambiguity (B = 0.603, 95% CI [0.150, 0.463], p <.001). Additionally, workplace alienation showed positive direct associations with role ambiguity (B = 0.268, 95% CI [0.195, 0.443], p <.001) and covert narcissism (B = 0.191, 95% CI [0.293, 0.426], p <.001). Mediated effects were also observed: perceived overqualification indirectly influenced workplace alienation via covert narcissism (B = 0.367, 95% CI [0.131, 0.273], p <.001) and via role ambiguity (B = 0.228, 95% CI [0.183, 0.513], p <.001). Conclusion Perceived overqualification significantly contributes to workplace alienation among nurses, with covert narcissism and role ambiguity acting as mediators. To mitigate these effects, healthcare organizations should implement targeted interventions such as structured role clarification, career development programs, and leadership strategies that enhance nurses’ sense of professional fulfillment. These strategies can improve job satisfaction, reduce turnover, and support workforce sustainability in healthcare settings. Clinical trial number Not applicable.